The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.enbuild.2020.109889
|View full text |Cite
|
Sign up to set email alerts
|

Occupant action patterns regarding spatial and human factors in office environments

Abstract: Since occupant behaviour impacts the energy performance of buildings, its study is relevant in order to bridge the performance gap. While the factors influencing occupant behaviour have been established, most studies have focused on those factors that motivate the action, such as environmental and temporal conditions. Contextual factors including spatial and occupant characteristics, which act as action moderators, remain a subject to explore. In this way, this article aims to identify patterns in the occupant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 82 publications
(118 reference statements)
0
11
1
Order By: Relevance
“…Vega et al [8] assessed various factors, including seven spatial factors (e.g., urban-rural gradient, city center, and village center), to develop a suitable policy for increasing the uptake of carbon emission reduction measures, and highlighted the importance of using spatial factors for designing energy policy frameworks. Marín-Restrepo et al [23] identified OB patterns in office environments through data analysis and the Chi-squared test based on spatial (e.g., spatial layout and occupant orientation relative to control elements) and human factors. Wilke et al [24] considered an independent variable that indicated whether an occupant lives in an urban/suburban area to simulate the starting probability of activities through a multinomial logit model.…”
Section: Review Of Methods For Considering Spatial Variation In Ob An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Vega et al [8] assessed various factors, including seven spatial factors (e.g., urban-rural gradient, city center, and village center), to develop a suitable policy for increasing the uptake of carbon emission reduction measures, and highlighted the importance of using spatial factors for designing energy policy frameworks. Marín-Restrepo et al [23] identified OB patterns in office environments through data analysis and the Chi-squared test based on spatial (e.g., spatial layout and occupant orientation relative to control elements) and human factors. Wilke et al [24] considered an independent variable that indicated whether an occupant lives in an urban/suburban area to simulate the starting probability of activities through a multinomial logit model.…”
Section: Review Of Methods For Considering Spatial Variation In Ob An...mentioning
confidence: 99%
“…Each group was homogenized to avoid the influence of sociodemographic factors in the spatial variation as shown in Table 1. The conditions for segmentation were the type of day (i.e., weekdays and weekends) and employment status-commonly used parameters in previous studies [19,20,23,24,50]. Groups 1 and 4 represent women with fulltime jobs; Groups 2 and 5 represent women with part-time jobs; Groups 3 and 6 represent unemployed women.…”
Section: Segmentationmentioning
confidence: 99%
“…Relationships between adaptation and spatial and adaptable building characteristics have already been investigated in other contexts (e.g. Schweiker and Wagner 2016, Marín-Restrepo et al 2020aand 2020b and in hospitals (Willems et al 2021). More insight is needed into the relationship between adaptation and building physical and spatial characteristics.…”
Section: Future Researchmentioning
confidence: 99%
“…It builds upon existing research in order to understand the influence of adaptation and perceived control on how indoor conditions are experienced (e.g. Humphreys et al 2013, Schweiker and Wagner 2016, Marín-Restrepo et al 2020a, 2020b. More specifically, it aims to contribute to filling the knowledge gap about whether and how different adaptation strategies influence the experience of indoor conditions differently.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the questionnaire were analyzed using hierarchical cluster analysis. A field study covering 85 office spaces within 11 buildings in Chile showed that occupants' preferences and behavior might also be influenced by their spatial location within a room or building, considering their opportunities (Marín-Restrepo, Trebilcock, & Gillott, 2020).…”
Section: Occupant's Preferencementioning
confidence: 99%